Pengaruh Model Pembelajaran Talking Stick Berbantuan Media Powerpoint Terhadap Hasil Belajar IPS Siswa Kelas VIII Di SMP Negeri 2 Gianyar - Melianawati, Ni Kadek Ary; Indrayani, Luh (Jurnal Pendidikan Ekonomi Undiksha, 2023)
The "Nonequivalent Control Group Design" is a quasi-experimental research design. This research was conducted to determine the effect of the talking stick learning model assisted by PowerPoint media on the social studies learning outcomes of VIII-grade students at SMP Negeri 2 Gianyar. 441 students were used as the population in this research, and the sampling was carried out with certain considerations, namely purposive sampling. The sample in this study was 40 students in the 8H class as the experimental class and 40 students in the 8J class as the control class. The data collection method used is the test method at the time of the test which is then analyzed using t-test analysis. The results demonstrated an effect of using a talking stick learning model assisted by PowerPoint on the social studies learning achievement of VIII-grade students at SMP Negeri 2 Gianyar. The result of the t-test shows a score of t 5.664 with a significant value of < 0.05 (0.000 < 0.05), so Ha was accepted and H0 was rejected.